Analysis of the low reading and writing capability of bilingual students in ‘sanggar bimbingan’ from a socio cultural aspect: case study in the lower grade of sanggar bimbingan sekolah indonesia kuala lumpur - Nikmah, Lina (ALKADIMAT, 2023)
This study aims to describe the reading and writing ability of lower-grade students of Sanggar Bimbingan Sekolah Indonesia Kuala Lumpur in using Indonesian at school and Malay in everyday environments. This research uses a qualitative approach with participatory action research methods as well as action research and interview data collection techniques. Researchers work alongside participants to identify problems, develop research questions, collect and analyze data, and implement solutions or actions based on findings. Based on the results of field experience, researchers found several difficulties for students in learning Indonesian, especially in spelling, reading a text, and writing sentences in Indonesian correctly. In this study, several factors were found that influenced the low reading and writing ability of lower-grade students of the Sanggar Bimbinngan Sekolah Indonesia Kuala Lumpur in socio-cultural aspects, such as the living environment, association, family, and economy.